Platelet-rich fibrin improves repair and regeneration of damaged endometrium in rats - Mao, Lele; Wang, XiaoXue; Sun, Yu; Yang, Mukun; Chen, Xing; Cui, Lei; Bai, Wenpei (Frontiers in Endocrinology, 2023)
Purpose: Intrauterine adhesion (IUA) is the most common cause of uterine infertility.This study was to evaluate whether fibrin-rich platelet (PRF) treatment can stimulate damaged endometrium regeneration in rats.Methods: First, hematoxylin and eosin staining(HE), scanning and transmission electron microscopy, ELISA assays were used to evaluate the microstructure of PRF.Then, mechanical damage was used to establish IUA rat model. A total of 40 SD female rats were randomized to three groups: PRF transplantation group, IUA group and Sham group. Rats were sacrificed at time of 3, 7 days, 14 days and uterus were obtained for further analysis. Finally, functional and histological recovery of the damaged endometrium was analyzed by pregnancy test, HE, Masson's staining and immunohistochemistry.Results: PRF has two distinct zones, platelets and fibrin zone. Long and narrow fibrin fibers interconnected with each other and formed a three-dimensional, flexible and elastic structure, platelets aggregates were trapped in fibrin fibers, each platelet is 2 associated with several fibrin fibers. PRF exudates promoted endometrial stromal cells proliferation and migration in vitro. PRF transplantation was beneficial for maintaining uterine structure and promoting endometrial luminal epithelium and endometrial glands regeneration, decreasing fibrosis areas in vivo.Intrauterine administration of PRF was demonstrated to be effective in preventing IUA and stimulating damaged endometrium regeneration in rats. This study provided a promising method not only for its potential in endometrial regeneration in human who suffers from uterine infertility but also may prevent IUA after intrauterine surgery in clinical cases.